2018
DOI: 10.1530/ec-17-0156
|View full text |Cite
|
Sign up to set email alerts
|

EDC IMPACT: Chemical UV filters can affect human sperm function in a progesterone-like manner

Abstract: Human sperm cell function must be precisely regulated to achieve natural fertilization. Progesterone released by the cumulus cells surrounding the egg induces a Ca2+ influx into human sperm cells via the CatSper Ca2+-channel and thereby controls sperm function. Multiple chemical UV filters have been shown to induce a Ca2+ influx through CatSper, thus mimicking the effect of progesterone on Ca2+ signaling. We hypothesized that these UV filters could also mimic the effect of progesterone on sperm function. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…In addition, our results showed that the two most efficacious bisphenols at 10 µM, BPG and BPAF, could both increase sperm penetration into a viscous medium, like the response induced by the endogenous CatSper ligands progesterone and PGE1 ( Figure 5), and induce acrosome reaction in capacitated human sperm cells, similar to the response induced by progesterone ( Figure 6). Again, this is in line with previous studies where other environmental chemicals activating CatSper were found to exert progesterone-like effects on human sperm function (34,(36)(37)(38)56).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our results showed that the two most efficacious bisphenols at 10 µM, BPG and BPAF, could both increase sperm penetration into a viscous medium, like the response induced by the endogenous CatSper ligands progesterone and PGE1 ( Figure 5), and induce acrosome reaction in capacitated human sperm cells, similar to the response induced by progesterone ( Figure 6). Again, this is in line with previous studies where other environmental chemicals activating CatSper were found to exert progesterone-like effects on human sperm function (34,(36)(37)(38)56).…”
Section: Discussionsupporting
confidence: 92%
“…It is known that chemicals in our environment, like UV-filters, can induce acrosomal exocytosis [25,26]. Such a mode of action may contribute (via the male partner) to the observed decline in fertility which has been described in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating the endocrine disruption potential are available since the assessment performed by the Danish Centre on Endocrine Disrupters (Table ). In a recent in vitro study assessing the potential effects of chemical UV filters on human sperm, no effects on sperm acrosome reaction, sperm penetration, proportion of hyperactivated sperm cells or sperm viability were observed …”
Section: Endocrine Disruption Potentialmentioning
confidence: 99%
“…In a recent in vitro study assessing the potential effects of chemical UV filters on human sperm, no effects on sperm acrosome reaction, sperm penetration, proportion of hyperactivated sperm cells or sperm viability were observed. 15 The following studies are available on the ECHA website (unpublished studies as cited by ECHA, 2019 5 ) in order to assess the potential of endocrine activity of octocrylene. A uterotrophic assay, which is a short-term screening test to evaluate the ability of a chemical to elicit biological activities consistent with agonists or antagonists of natural oestrogens, was carried out in immature female rats (10 per dose) treated with octocrylene at doses of 250 and 1000 mg/kg bw/day via oral route.…”
Section: Endocrine Disruption Potentialmentioning
confidence: 99%
See 1 more Smart Citation